Examining The Effect of Sustainability Report Disclosure to Firm Value: A Study Based on Listed Public Companies in Indonesia Stock Exchange - Mulyana Chandra Hadiati; Muhammad Brilian Wahyudyatmika (Dinasti International Journal of Economics, Finance & Accounting, 2023)
Companies that mitigate and improve the environment can take advantage of this as a marketing tool in general. Consumers will support companies that have a positive impact on their surroundings. One of the tools that can be used as a form of responsibility and marketing tool is a sustainability report. Sustainability report are reports published by organizations or companies that explain the economic, environmental, and social impacts as result of their operating activities. The report also explains about corporate culture and governance as well as its relationship with the company's strategy and commitment to maintain the sustainability of the triple bottom line (people, planet, profit). Sustainability reporting disclosure index (SRDI) are measured from 89 listed public companies in Indonesia. Regression analysis took place for examining the effect of SRDI to the corresponding firm value represented by Tobin’s Q. Only certain limited sample data showed that there’s a significance effect between sustainability report disclosure and firm value. Enterprises who haven’t disclose their sustainability report still worth high value in share trade. This condition occurs due to investors' decisions to invest are influenced by media coverage, economic conditions, and changes in stock prices.